PERBANDINGAN KEEFEKTIFAN PENDEKATAN PROBLEM POSING DAN PROBLEM BASED LEARNING DITINJAU DARI KEMAMPUAN LITERASI MATEMATIS SISWA SMP KELAS VIII - Hana’ Aulia Dewi , Endang Listyani (Universitas Negeri Yogyakarta, 2018)
AbstrakPenelitian ini bertujuan untuk mengetahui keefektifan pendekatan problem posing dan pendekatan problem based learning ditinjau dari kemampuan literasi matematis siswa SMP kelas VIII dalam pembelajaran matematika, serta mengetahui perbedaan keefektifan antara pendekatan problem posing dan problem based learning ditinjau dari kemampuan literasi matematis siswa SMP kelas VIII. Jenis penelitian ini adalah eksperimen semu dengan desain pretest and posttest experimental group design. Data dianalisis dengan cara: one sample t-test untuk menguji keefektifan pendekatan problem posing dan pendekatan problem based learning serta independent sample t-test untuk menguji perbandingan keefektifan pendekatan problem posing dan pendekatan problem based learning, dengan = 0,05. Hasil analisis menunjukkan bahwa pendekatan problem posing dan pendekatan problem based learning efektif ditinjau dari kemampuan literasi matematis siswa SMP kelas VIII, serta tidak ada perbedaan keefektifan antara pendekatan problem posing dan pendekatan problem based learning ditinjau dari kemampuan literasi matematis siswa SMP kelas VIII. Kata kunci: keefektifan, problem posing, problem based learning, kemampuan literasi matematis AbstractThis research aimed to find out the effectiveness of problem posing and problem based learning approaches in regards to mathematics literacy ability of students grade VIII junior high school; and find out the differences in the effectiveness between problem posing and problem based learning approach in regards to mathematics literacy ability of students grade VIII junior high school.The type of this research was quasi experimental with pretest and posttest group design. The data were analyzed by means of: one sample t-test which was used to test the effectiveness of problem posing approach and problem based learning approach and independent sample t-test which was used to test the differences in the effectiveness between problem posing and problem based learning approach. The results showed that problem posing and problem based learning approaches is effective in regards to mathematics literacy ability of students grade VIII junior high school; and there is no difference in effectiveness between problem posing and problem based learning approach in regards to mathematics literacy ability of students grade VIII junior high school. Keywords: effectiveness, problem posing, problem based learning, mathematics literacy ability